2(9x+7)-6x=3(4x+2)-9

Simple and best practice solution for 2(9x+7)-6x=3(4x+2)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9x+7)-6x=3(4x+2)-9 equation:


Simplifying
2(9x + 7) + -6x = 3(4x + 2) + -9

Reorder the terms:
2(7 + 9x) + -6x = 3(4x + 2) + -9
(7 * 2 + 9x * 2) + -6x = 3(4x + 2) + -9
(14 + 18x) + -6x = 3(4x + 2) + -9

Combine like terms: 18x + -6x = 12x
14 + 12x = 3(4x + 2) + -9

Reorder the terms:
14 + 12x = 3(2 + 4x) + -9
14 + 12x = (2 * 3 + 4x * 3) + -9
14 + 12x = (6 + 12x) + -9

Reorder the terms:
14 + 12x = 6 + -9 + 12x

Combine like terms: 6 + -9 = -3
14 + 12x = -3 + 12x

Add '-12x' to each side of the equation.
14 + 12x + -12x = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0
14 + 0 = -3 + 12x + -12x
14 = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0
14 = -3 + 0
14 = -3

Solving
14 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x+7+2x=5 | | 2(1+x)/3=x+1 | | y=-1/2*-4+2 | | 180-.14=.29 | | 3x+7+x+8=39 | | 7/2x+1/2=27.5+9/2x | | -14=2(2x+3) | | 22x+7-27x=1-9 | | 16-x=4(4-3x) | | 6-5*3=y | | 3+4x=-3x+87 | | 7x+15-6x=-5-12 | | 6-5*2=y | | -18=3(y+1) | | -7x+7x=-x | | 71y=5(14y+29) | | x^2+3x+4=6 | | -7(-10+3)=x | | 6-5*1=y | | X^4-26x^2-160=0 | | 7/2x+1/2=271/2+9/2x | | 4(4a-1)=28 | | 32-5t=3t | | 7x+y=27 | | 14-.2(j-10)=.4(25+j) | | y=-6+5*1 | | 2+2=13-3x | | -30+-15d=24+21d | | 4-13x=8+x | | 9x+8(6/7x-1)=1 | | X-5.6=1.2 | | -3/2*8+4 |

Equations solver categories